Resident's trust and participation in the localisation of Sustainable Development Goals (SDGS) in Malaysia / Farah Adilla Ab Rahman , Radduan Yusof and Mohd Idham Mohd Yusof - Ab Rahman, Farah Adilla; Yusof, Radduan; Mohd Yusof, Mohd Idham (2021)
The local government is seen as a suitable governance entity in intensifying further the United Nations SDGs programs to the community. Using the bottom-up approach, the resident associations will enable the community to participate with the local government in dealing with local issues that affect their neighbourhood. Hence, the local government must improve its responsibility to gain trust for the continuation of resident participation. Trust is necessary for creating the conditions of good government and being a prerequisite for a representative form of governance (Bhakta, 2010). Moreover, the absence of trust can lead to a lack of democratic participation, reduced willingness to get engaged in other civic activities, and broader problems of governmental legitimacy (Downe, Cowell, Chen, & Morgan, 2013). A decrease in the public trust for the government occurs when there is a lack of participation during governance processes, decreasing the unity of the society and the ability to overcome common issues (Makorere, 2012). Accordingly, this paper aims to provide a literature review on SDGs implementation through grassroots collaboration and to discover the link between residents' trust and participation in supporting the LA21 and SDGs related program implementation in Malaysia. Based on the literature analysis, this study also proposes the conceptual framework on the relationship between trust and resident participation in implementing SDGs in Malaysia.